Cancer registration in the Middle East, North Africa, and Turkey (MENAT) region: A tale of conflict, challenges, and opportunities - Abdul-Sater, Zahi; Mukherji, Deborah; Adib, Salim M.; Shamseddine, Ali; Abu-Sitta, Ghassan; Fadhil, Ibtihal; Sullivan, Richard; Omari, Amal Al; Saleh, Shadi; Taher, Ali (Frontiers in Oncology, 2022)
Cancer registration is a core component of national and regional cancer control strategies. In the Middle East, North-Africa and Turkey (MENAT) region, capacity and resources for cancer registration is variable and shaped by multiple contextual challenges. This viewpoint maps out practical recommendations around cancer registration, in an attempt to inform cancer control planning, policy, and implementation. The recommendations laid out in this viewpoint are informed by the discussions held at the Initiative for Cancer Registration in the MENAT (ICRIM) virtual workshop, which convened registry managers, policy makers, and international agencies from 19 countries in the MENAT region. The discussions were distilled in four categories of recommendations, revolving around cancer registration procedures, collaborative governance, putting cancer registration on the map, and capacity building. This viewpoint provides a much-needed mapping of practical recommendations around cancer registration, informed by direct key stakeholders in the region. These practical recommendations offer a road map for policy making, cancer control planning, and future regional capacity strengthening initiatives.